156k views
3 votes
9. How does the function y = 2" compare to the function y = (-)" Include at least three comparisons for credit. (3 points) B I U EE

User Taran J
by
5.4k points

1 Answer

5 votes

Step-by-step explanation


\begin{gathered} \text{Given the below function} \\ y=2^x \\ \text{y = (}(1)/(2))^x \\ \text{According to the law of indicies} \\ ((1)/(x))^a=x^(-a) \\ \text{Therefore,} \\ y\text{ = (}(1)/(2))^x=2^(-x) \\ y=2^x \\ \text{y = 2}^(-x) \\ The\text{ second function is an inverse of the first function} \end{gathered}

ALSO

User Arika
by
4.5k points